Tokophobia and associated factors in pregnancy: A community-based cross-sectional survey - Adeniyi Abiodun Adewunmi; Lateef Adekunle Akinola; Ayokunle Moses Olumodeji; Gideon Ntieno Inyangudo; Tawaqualit Abimbola Ottun; Abiodun Samuel Adegoke; Justina Ucheojor Onwuka; Bolanle Adeyemi Ola (PLoS ONE, 2026)
Background Fear of childbirth (tokophobia) impacts maternal health, yet its prevalence and associated factors remain underexplored in Lagos. This study aimed to determine the prevalence of tokophobia and its associated risk and psychological factors. Methods This community-based cross-sectional survey, conducted in Lagos, over a 4-month period, involved 855 pregnant women attending antenatal care at Lagos’ 57 flagship primary health care centers (PHCs). Fifteen eligible pregnant women who were consecutively selected from each PHC’s antenatal clinic list, had in-depth interviews using a structured questionnaire consisting of the Wijma Delivery Expectancy Questionnaire (W-DEQ A) for fear of childbirth, the Depression Anxiety Stress Scales (DASS-21), and the Generalized Anxiety Disorder 7-item (GAD-7) scale. Data was analyzed with appropriate descriptive and inferential statistics including trend-based tests for ordinal variables and multivariable logistic regression modeling ordinal predictors at <0.05 significance level. Results The women’s mean age was 28.37 years and majority were multigravida, in their third trimester with secondary level of education. Fear of childbirth levels revealed 7.7% with low fear, 38.9% with moderate fear, 48.4% with high fear, and 4.9% with severe fear of childbirth (tokophobia). Of those with tokophobia, 35.7% had primary tokophobia, and 64.3% had secondary tokophobia. Comparative analysis showed no significant differences in most demographic or obstetric characteristics between women with and without severe fear of child birth, although younger age was significantly associated with severe tokophobia . Women with severe tokophobia had significantly higher anxiety and stress levels on the DASS-21, while the GAD-7 was not significantly associated after accounting for ordinal trend. The distribution of fear-of-childbirth severity also differed significantly by gravidity, prior vaginal birth, and number of living children. In multivariable analysis, increasing anxiety severity on the DASS-21 remained independently associated with severe tokophobia, whereas stress and GAD-7 categories did not. Conclusion This study highlights the significant presence of tokophobia among pregnant women in Lagos, aligning with global evidence while emphasizing the need for culturally tailored research. Routine screening for tokophobia using standardized tools and assessment of anxiety symptoms during antenatal care should be considered for integration into antenatal care, along with targeted counseling and psychological support services following further research.